Design and development of metoprolol succinate sustained release tablet using Eulophia herbacae and Remusatia vivipara tuber mucilage as novel drug release modifiers. (29th July 2022) - Sharma, Ganesh; Bhurat, Mayur; Shastry, Vijay; Shrivastava, Birendra
ABSTRACT: The present research was aimed to develop Metoprolol succinate sustained-release tablet by wet granulation using novel polymers Eulophia herbacae  and Remusatia  vivipara  tuber mucilage as release retardants. The formulations were prepared using a 3 2  full factorial design. In the current research, two factors were tested each at three levels. The concentration of  Eulophia herbacea  mucilage (X1) and  Remusatia vivipara  mucilage (X2) were selected as independent variables, and swelling index, t75  of % cumulative drug release, and drug content were selected as dependent variables. The prepared tablets were evaluated by weight variation test, hardness, friability, swelling index, drug release, and drug content. The optimized tablet was compared with reference formulation PROLOMET XL 100. The drug release kinetics study was performed by various models. It reveals that formulation follows anomalous diffusion (non-fickian) pattern and follows both diffusion-controlled and swelling controlled mechanisms of drug release.